The Effectiveness of using the Kitab Muhawarah in Enhancing Arabic Speaking Proficiency in Malaysia - Muhamad Solehudin; Nurhanifansyah, Nurhanifansyah; Syaheed Kholid (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2024)
This study explores the effectiveness of Kitab Muhawarah in enhancing maharah kalam (speaking proficiency) among Arabic language learners in Malaysia, addressing the existing challenges in Arabic education, particularly the need for more resources focused on conversational skills. The research aims to assess how Kitab Muhawarah, a textbook emphasizing practical dialogues, contributes to students' ability to speak Arabic fluently and confidently. The study utilized a qualitative approach, gathering data through in-depth interviews, classroom observations, and document analysis. A sample of 60 students from Maktab Mahmud Yan participated in the study over three months, during which their progress in speaking proficiency was monitored. The findings reveal significant improvements in students' speaking confidence, fluency, and the application of Arabic vocabulary in real-life contexts. This research highlights the importance of incorporating dialogue-based learning into Arabic language instruction, presenting Kitab Muhawarah as a valuable tool for bridging the gap between theoretical knowledge and practical use.